Generation of transgenic chicken through ovarian injection - Jinghua Jiang; Caiying Wang; Xuguang Du; Fei Gao; Sen Wu (Animal Models and Experimental Medicine)
Abstract Background Traditional DNA microinjection methods used in mammals are difficult to apply to avian species due to their unique reproductive characteristics. Genetic manipulation in chickens, particularly involving immature follicles within living ovaries, has not been extensively explored. This study seeks to establish an efficient method for generating transgenic chickens through ovarian injection, potentially bypassing the challenges associated with primordial germ cell (PGC) manipulation and fertilized egg microinjection. Methods Hens were anesthetized and underwent a surgical procedure to access the ovary for DNA injection into immature follicles. The study used liposomes to deliver GFP‐expressing plasmids at various dosages. After injection, hens recovered, and their eggs were fertilized through artificial insemination. Results Transgenic chickens were successfully generated in one generation without needing G0 founders. The injection of 20 μg plasmid yielded the highest transgenic efficiency at 12.1%. GFP‐positive embryos were confirmed through microscopy, and successful transgene expression was validated at the tissue level using immunostaining. TERT and GFP elements introduced in the G1 generation resulted in 4.1% positive transgene rates, as confirmed by PCR and Southern blotting. Conclusion This ovarian injection method offers a promising alternative for avian genetic manipulation, bypassing complex PGC procedures and enabling direct generation of G1 transgenic chickens. This technique simplifies the transgenic process for chickens and has the potential to be adapted for other avian species, especially those without established PGCs culture systems.